The Advantages and Disadvantages of Divorce Cooling-off Period System and the Way to Improve It - Wang, Zihan (International Journal of Global Economics and Management, 2024)
China has added the divorce cooling-off period system in the Civil Code of Marriage and Family. The legislators created this system in the original intention of easing the phenomenon of hasty divorce and strengthening the protection of minors in family relations. There is no denying that the starting point of this system is good, but the system has also exposed some drawbacks in the practice process. Whether the cooling-off period system of divorce in the Civil Code is necessary, how to establish a corresponding supporting system of the cooling-off period system of divorce in the Civil Code, and effectively regulate the social problems derived from the system are the issues we need to think about.